Multimodal Analysis of Innisfree’s Brand History - Vanessa Velancia Prajogo; Setefanus Suprajitno (Kata Kita: Journal of Language, Literature, and Teaching, 2020)
Fierce competition in increasing market share growth prompts companies to strive to create a memorable brand identity. One common method adopted by some companies is using a video advertisement, which contains the message they want to convey about their product or brand. This message is intended to persuade people who see the advertisement to buy their product. In doing so, companies usually use the visual, linguistic, spatial and other semiotic resources, often referred to as a semiotic mode. Through the case study of Innisfree’s video advertisement “Brand History,” we analyze how Innisfree uses linguistic, spatial, and visual mode for creating a message that enables consumers to remember and to persuade them buy its product. Our findings show that the message in the video advertisement is that Innisfree is a beauty product that upholds nature as its ingredients, has high quality, and preserves the environment where it takes its ingredients. Key Words: Advertisement, Persuasion, Modes, Verbal and Non-verbal expressions.